2018
DOI: 10.1116/1.5035422
|View full text |Cite
|
Sign up to set email alerts
|

Obtaining low resistivity (∼100 μΩ cm) TiN films by plasma enhanced atomic layer deposition using a metalorganic precursor

Abstract: Low resistivity (∼100 μΩ cm) titanium nitride (TiN) films were obtained by plasma enhanced atomic layer deposition using tetrakis(dimethylamido)titanium and a nitrogen/argon plasma mixture. The impact of process parameters on film crystallinity, oxygen contamination, and electrical resistivity was studied systematically. A low background pressure during the plasma half-cycle was critical for obtaining low resistivity. The low resistivity films were highly crystalline, having (001) oriented columnar grains. Oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…Based on the sheet resistance measurements and the film thickness extracted from TEM, the TiN x O y effective resistivity was calculated: 484 ± 8 μΩ cm for G1 and 202 ± 4 μΩ cm for G2 samples, so the FGCD process decreased the TiN x O y resistivity more than twice. The resistivity of the FGCD-treated films was close to average values reported for ALD-grown TiN: 70–300 μΩ cm. , Therefore, our result appeared surprisingly low as the films were grown using the ALD reactor without load lock with a considerable amount of residual oxygen, so the O-content and resistivity of thus obtained TiN x O y films were supposed to be large. TEM also revealed V-shaped nanocrystallites of TiN x O y embedded in the amorphous TiN x O y film of the G2 samples, and similar features have been reported by others .…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Based on the sheet resistance measurements and the film thickness extracted from TEM, the TiN x O y effective resistivity was calculated: 484 ± 8 μΩ cm for G1 and 202 ± 4 μΩ cm for G2 samples, so the FGCD process decreased the TiN x O y resistivity more than twice. The resistivity of the FGCD-treated films was close to average values reported for ALD-grown TiN: 70–300 μΩ cm. , Therefore, our result appeared surprisingly low as the films were grown using the ALD reactor without load lock with a considerable amount of residual oxygen, so the O-content and resistivity of thus obtained TiN x O y films were supposed to be large. TEM also revealed V-shaped nanocrystallites of TiN x O y embedded in the amorphous TiN x O y film of the G2 samples, and similar features have been reported by others .…”
Section: Resultssupporting
confidence: 78%
“…Magnetron sputtering, ,, reactive sputtering, pulsed laser deposition, and atomic layer deposition (ALD) are the major technologies to produce TiN x O y thin films as they do not require elevated temperatures while providing good conformity. ,, The self-limiting nature of the ALD growth and the ability to grow on the shaded and even upside-down surfaces make this technology more favorable for certain applications. ALD provides unsurpassed accuracy of the film thickness and uniformity; therefore, we believe that this technology is a highly promising route to develop TiN x O y resistors for high-frequency integrated circuits in the future. However, compared to magnetron sputtering, ALD usually does not have high vacuum, which may result in a less precisely defined oxygen content in TiN x O y films due to the admixture of residual oxygen in the ALD chamber during the growth.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, previous studies also showed that the crystallite size of fcc CoN can be significantly decreased with nitrogen partial pressure [39]. Hence, due to enhanced electron scattering at grain boundaries [42], an increase in electric resistivity with increasing nitrogen partial pressure is expected. The differences in magnetoionic behavior of distinct Co-N systems (i.e., between CoN and Co 3 N) are dominated by their dissimilar stoichiometries, crystal structures, and bonding.…”
Section: Introductionmentioning
confidence: 91%
“…The main aims are further improvement of the material properties and the usage of metal-organic precursors instead of halides for sensitive applications (e.g., TiN ALD using Ti(NMe 2 ) 4 instead of TiCl 4 ). 98,99 Some new conductive nitrides are also reported such as VN x , 66 CoN x , 41 and SnN x , 62 and the expectation is that in principle all stable nitrides should be feasible by plasma ALD. Superconductivity is a property that could become more of interest because of quantum-computing applications, and the demonstration of plasma ALD of NbN with good superconductivity is worth mentioning.…”
Section: Nitrides and Carbidesmentioning
confidence: 99%